Analisis Kebutuhan Tempat Tidur Di Bangsal Merak RSUP Dr. Kariadi Semarang Tahun 2022-2024 - SABRAN SABRAN; M. Kurniawan; S Deddy Setiadi (Indonesian Journal Publisher, 2022)
The hospital as a complete health service unit is currently undergoing development where various standards are used to see the effectiveness and efficiency of health services, some of which are. are BOR and LOS. This research was conducted at RSUSP Dr. Kariadi Semarang, namely in three wards; Basic Peacock, Peacock 1, and Peacock 2. The data used in this study are data from 2017 to 2019. The method used in this study is a quantitative descriptive research method. It is known that the number of bed capacities in Dr. Kariadi did not experience an increase in the study year. In addition, the number of effective days in the three wards varied with the condition that the number of treatment days was predicted to decrease. On the other hand, the BOR is too high so it is necessary to add more beds.